Artin Exponent for the Special linear group SL(2,pk) where pk = 9, 25 and 27 (Journal of the College of Basic Education, 2022)
In this paper we calculate the Artin exponent for the Special linear group SL(2,pk) where p is 9, 25 and 27, from the cyclic subgroups of this groups which is equal to the order of the group.